Polityka Związku Gmin Karkonoskich a zasada zrównoważonego rozwoju - Markowska, Katarzyna (Policy of the Karkonosze Mountains Municipality Union and Sustainable Development, 2007)
The article is an attempt to present the benefits of globalization and possibilities for our country ensue from gaining and correct spending union funds. Following connections among the various levels, such as: municipality, administration, district, region, country, and the European Union. It is certain that the strategy of the sustainable development is a priority for our country's development and the process of globalization in the world economy. The aims of strategy entitled "Policy of the Karkonosze Mountains Municipality Union" and the achievement of social, economic, and environmental changes, which are positively evaluated from the point of anthropocentric system of values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 403-410